Influence of 3-acetyl-5-hydroxy-2-methylindole on glioma cell proliferation and metabolism - Panada, Jan U.; Klopava, Valeriya A.; Kulahava, Tatsiana A.; Faletrov, Yaroslav V.; Horetski, Matvey S.; Frolova, Nina S.; Koran, Siarhei V.; Fomina, Elena G.; Shkumatov, Vladimir M. (Journal of the Belarusian State University. Chemistry, 2022)
A 3-acetyl analogue of 5-hydroxyindole was synthesised and evaluated for its effects on rat C6 glioma cell functions. It was found that 3-acetyl-5-hydroxy-2-methylindole at 10 μmol/L led to a sharp reduction of mitochondrial membrane potential, induction of autophagy and decrease of proliferation of C6 glioma cells. The compound’s effect was comparable to that of rotenone, an inhibitor of cell respiration.
Keywords: 5-hydroxyindole; glioma; autophagy; mitochondrial transmembrane potential; rotenone